SISTEM INFORMASI E-COMMERCE BERBASIS WEBSITE MENGGUNAKAN MODEL UCD PADA PASAR KEPANJEN KABUPATEN MALANG - Widya Mawarni, Dilla; Agustina, Rini; Susanto, Gaguk (Department of System Information, 2025)
The development of information technology and e-commerce has changed people’s shopping patterns, allowing consumers to shop online without going to physical stores. Kepanjen market in Malang regency is facing challenges from a decline in the number of buyers due to increasing interest in online shopping, especially after the pandemic. To solve this problem, this research offers a website-based e-commerce information system with a UCD approach, which gives traders in the Kepanjen market the opportunity to sell goods boldly and reach more buyers. After going through the design and evaluation stages using black box testing, this system was tested with a user acceptance test which obtained a score of 81.9%, which is included in the category of strongly agreeing with the existence of this information system.